TINJAUAN YURIDIS PEMULANGAN ANAK-ANAK DIBAWAH UMUR 10 TAHUN WARGA NEGARA INDONESIA EKS ISIS (ISLAMIC STATE OF IRAQ AND THE LEVANT) BERDASARKAN HUKUM PERLINDUNGAN ANAK - Ryandi Manuel Sumedi; Rasji Rasji (Jurnal Hukum Adigama, 2021)
Many Indonesian citizens ex ISIS (Islamic State of Iraq and The Levant) had the desire to return to Indonesia, thus making a lot of different arguments to the community. Eventually, President Joko Widodo decided not to give permission to 689 former ISIS Indonesian citizens to return to Indonesia on February 12, 2020. However, a new discourse emerged to return the children of former ISIS combatants who were under 10 years old back to Indonesia. Then what is the state's responsibility for the repatriation of children of Indonesian citizens ex ISIS based on child protection law? The method that will be used in this research is normative legal research, this research is prescriptive, the type of data used is secondary data, the data collection technique used is a literature study, in this study the approach used is a statute approach. and used deductive method as a data analysis technique. The results of the study show that the Indonesian government has the responsibility and obligation to repatriate the children of Indonesian citizens who were ex-ISIS. This is due to the existing laws and regulations in Indonesia, especially the Child Protection Act which states that the government has an obligation to provide special protection to children who are victims of terrorist networks. In addition, the rehabilitation process and so on have been regulated in the relevant Ministerial Regulation. Therefore, it is better for the Indonesian government to repatriate Indonesian ex-ISIS children under the age of 10 years by arranging the repatriation procedures carefully.